Differentiating Instruction for Differently-Able English Language Learners in a Remote Classroom - De Jesus, Olga (R&E-SOURCE, 2020)
The traditional teaching methods of delivering instruction by lecture, giving students practice work and reviewing the correct answers during assessment do not work for all students. Gregory & Chapman (2013), stated that educators can no longer teach "the lesson" and hope that everyone gets it. Even though this method is “uniform” and consistent, all learners are different in terms of how they grasp a concept. As if this is not challenging enough, now educators have to instruct virtually, adding another challenge for the Differently-Able English Language Learners. It is crucial for school leaders and educators to address these challenges, because the transition to a virtual classroom can put already-struggling students even further behind.